Dampak Pandemi Covid-19 pada Pengelolaan Usaha Mikro Kecil Menengah (UMKM): (Studi Kasus UMKM Rumah Ety di Kota Bengkulu) - Pebri i Yanto Syaputra; Titi Darmi; Rosidin (Jurnal Manajemen Publik dan Kebijakan Publik (JMPKP), 2022)
This study examines the Impact of the Covid-19 Pandemic on the Management of Micro, Small and Medium Enterprises (MSMEs) (a case study of the micro, small and medium enterprises of Rumah Ety in Bengkulu City). The formulation of this research problem is to determine the Impact of the Covid-19 Pandemic on the Management of Micro, Small and Medium Enterprises (MSMEs) (a case study of the micro, small and medium enterprises of Rumah Ety in Bengkulu City). The purpose of this research is what are the impacts and how are the efforts made in the management of Micro, Small and Medium Enterprises (MSMEs), the Impact of the Covid-19 Pandemic on the Management of Micro, Small and Medium Enterprises (MSMEs) (case study of micro, small and medium enterprises Rumah Ety in Bengkulu City). Researchers used qualitative descriptive research methods. By using a SWOT analysis approach. The data analysis technique used is data reduction, data presentation and conclusion drawing. The results of this study explain the impact of the Covid-19 Pandemic felt by Rumah Ety MSMEs, namely the difficulty of selling directly or face to face with consumers, thereby reducing sales turnover from Rumah Ety. The efforts made by Rumah Ety MSMEs are to take advantage of the opportunities that exist in the midst of the Covid-19 Pandemic, and maintain business with the strengths of Rumah Ety. It is hoped that in this study the Rumah Ety MSME can improve the quality of management performance in managing the Rumah Ety business, further optimize the implementation of SWOT analysis, further maintain the superiority of the products produced so that they are more attractive to consumer buying, follow market developments, so that they can continue to survive in business competition and Rumah Ety's Micro, Small and Medium Enterprises (MSMEs) are expected to make more use of technological advances and social media to further support product marketing.